Effect of treatment modality on quality of life among patients with urinary bladder cancer. Issue 2 (21st December 2021) - Nowroozi, Ali; Abbasi, Behzad; Amini, Erfan; Nowroozi, Mohammad Reza; Moghadam, Solmaz Ohadian
Abstract: Bladder cancer is the second malignancies of the urinary system and negatively affect the patient's quality of life (QoL). The aim of this study was to evaluate the QoL of patients with urinary bladder cancer in terms of physical, psychological, social and environmental aspects. From January 2019 to December 2020, a cross‐sectional survey was accomplished using the World Health Organization Quality of Life Brief Version questionnaire to assess QoL of bladder cancer patients in terms of physical, psychological, social and environmental aspects. A multiple linear regression model was developed to assess the associations of clinical and demographic variables and treatment modalities with the QoL domains. No statistically difference between age, and comorbidities (i.e., diabetes mellitus, hypertension, smoking and body mass index) and the patients' QoL was observed. There was a significant direct correlation between QoL and health satisfaction ( p < 0.001, Fisher's exact test). Neither overall QoL nor satisfaction of health status were correlated with the use of urostomy ( p = 0.589 and 0.436, respectively), and domain scores of patients with urostomy were comparable to those without, in all four domains. None of the treatments were associated with a variation in the environment score. Patients who only underwent trans‐urethral resection of bladder tumour had statistically higher scores in the other three domains (i.e., physical, psychological and social relations), while scores of patients who underwent radical cystectomy (RC) were significantly lower in those domains. Patients who received either chemotherapy or radiotherapy did not differ in any of the domains from those who did not. To conclude, according to the results, the patient‐related factors (e.g., age and comorbidities) were not associated with the individuals' QoL of bladder cancer patients, while disease‐related factors—namely tumour grading and treatment modality—gained statistical significance. Moreover, we found that different QoL domains (physical health and psychological in specific) were highly correlated in our study population.